EFL Learners' Experiences with Flipped Classroom: A case study of students in the English Education Department - Alvina; Desy Rusmawaty; Aridah; Sunardi; Weningtyas Parama Iswari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The flipped classroom approach has garnered considerable attention in EFL higher education due to its capacity to enhance students' autonomy, engagement, and language proficiency. Grounded in self-regulated learning theory, this study examines the experiences of EFL students in flipped learning environments, focusing on the perceived advantages and challenges as well as their implications for teaching practice. This qualitative case study was conducted at the English Education Department at Mulawarman University and involved five third-year undergraduate students (aged 20–22) who had participated in flipped teaching for Phonology and Pronunciation courses during the 2023/2024 academic year. Data were gathered through semi-structured interviews and analysed using the six-phase thematic analysis proposed by Braun and Clarke (2006). Findings indicate that all participants (5/5) reported improvements in pronunciation, while most participants (4/5) experienced enhanced reading comprehension as well as increased speaking fluency and confidence. Pre-class exposure to multimedia resources improved students' readiness, classroom confidence, and engagement. In addition, students developed essential self-regulated learning strategies, including time management and autonomous inquiry. However, several challenges were identified. Three out of five participants reported inconsistent motivation and difficulties in managing time, while two participants experienced challenges in understanding course materials independently without direct teacher support. These findings suggest that students may not be fully prepared for complete autonomous learning and highlight the importance of structured scaffolding in flipped classroom implementation. The study reveals that the successful implementation of flipped classrooms in EFL contexts requires careful consideration of students' self-regulatory capacities, scaffolding needs, and equitable access to learning resources. Therefore, teachers should provide structured and varied instructional materials to maximize the effectiveness of flipped learning. Further research involving larger and more diverse samples, as well as the inclusion of teachers’ perspectives and measurable learning outcomes, is recommended to extend the understanding and applicability of flipped classroom practices.